Pembaharuan Single Line Diagram LVMDP Menggunakan Aplikasi Autocad di Departement Maintenance PT GS Battery Karawang Plant - Raka Ulfi; Dian Budhi Santoso (Universitas Islam Lamongan, 2022)
Analysis study Single line diagram drawing or what can be called Single Line Diagram analysis, is intended to obtain an updated image at PT GS BATTERY KARAWANG PLANT, previously a Single Line Diagram image of all buildings in PT GS BATTERY KARAWANG PLANT, which was last updated in 2016, while the pictures and tools in the field have changed a lot because the pictures and tools in the field have had a lot of components replaced by employees at the factory. Therefore, do a total update in 2021 by going down to the field and then implementing it into the drawing using the AutoCAD application. Autocad is a software application that functions to assist with computer assistance (CAD) and preparation, both in 2D and 3D formats. Components in the field, namely MCB, MCCB, NFB, etc. Due to the absence of information by employees after making changes, these components have changed a lot in the LVMDP panel box.